2009
DOI: 10.1007/s11747-009-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Brand related information as context: the impact of brand name characteristics on memory and choice

Abstract: Consumer exposure to new brand names can occur in contexts with or without brand information being present. Whereas previous research has examined the effects of brand name characteristics (association set size and word frequency) on memory in the presence of brand information, this paper also assesses brand name effects in contexts without brand related information and extends it to brand consideration and choice. Two different processes are found to be operating as consumers retrieve brands and make a choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
1
26
0
2
Order By: Relevance
“…Further research could empirically test associative and propositional processes as a mediator to verify the sub-brand attitude formation processes that underline affect transfer. Related to that, recent research has suggested an alternative mechanism that explains affect transfer based upon the concepts of diagnosticity and implicit memory (Samu and Krishnan 2010). Future research may examine the diagnostic effect of family brand name on sub-brand evaluation and consideration set.…”
Section: Discussionmentioning
confidence: 99%
“…Further research could empirically test associative and propositional processes as a mediator to verify the sub-brand attitude formation processes that underline affect transfer. Related to that, recent research has suggested an alternative mechanism that explains affect transfer based upon the concepts of diagnosticity and implicit memory (Samu and Krishnan 2010). Future research may examine the diagnostic effect of family brand name on sub-brand evaluation and consideration set.…”
Section: Discussionmentioning
confidence: 99%
“…Because the different recognition measures are thought to reflect unrelated underlying mechanisms they are often considered to be qualitatively different and not considered to be part of a hierarchy or continuum of recognition (Gardiner and Parkin 1990;Yonelinas 2002). While recent advertising studies appear to predominantly utilize measures of familiarity recognition (i.e., Peters and Leshner 2013;Lee et al 2013;Walsh et al 2013;Liu et al 2013), this may not always be the best measure for what ads actually do for brands: create brand associations (e.g., Samu and Krishnan 2010). Going forward, work utilizing recognition memory should be considerate of this distinction and how different characteristics of recognition memory may interact with audience-level (e.g., the media activity SEEING THE BIG PICTURE 181 or knowledge/traits) and ad-level variables (e.g., ad context or features) in separate ways.…”
Section: Discussionmentioning
confidence: 99%
“…Leiser and Drori 2005;Samu and Krishnan 2010). Moreover, media coverage is known to be an important determinant of the public's attitudes towards the causes of damaging economic events (Carroll and McCoombs 2003;Leiser and Drori 2005).…”
Section: H2mentioning
confidence: 99%